(3cJGH GdfHGJs - (3CMeO Hf OGhO Hf hffO GdOjfhQj, CHh MfjaI , GdOjfhQj,J (B282 (3g` s
(3ChdgG (B:s
(3hgPG HGH LeYJ ajg CMSf eG MVQfi PcQg ef hUa hef Ci GdTLQ jNJGQ hcja jbOM HgG s
(3BNQgG (B:s
(3hgh CHjV HWHNg GdfGS ai Chd fHSI aEPG jHS WGQJ dg HQGYeg hLQM efg eKd GfJgi eG fbdJg ef cJGH GdfHGJ JeJ HGdNjQ Je s
(3bWYI efgs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B123s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1466s
Keywords: (3GddZIs